Wound-Induced RNase Activity in Sweet Potato : EVIDENCE FOR REGULATION AT TRANSCRIPTION - Sacher, Joseph A. (1982)
Upon wounding of sweet potato (Ipomea batatas, Lam. var. Puerto Rico) RNase activity increases rapidly following a 4-hour lag, peaks in 24 hours, and then declines. Cycloheximide inhibits induction indicating that increased activity is probably due to de novo synthesis. The half-time (t(0.5)) for RNase degradation in presence of cycloheximide (1.8 hours) is constant throughout the rise and decline in RNase activity. Induction is not affected by exogenous ethylene, but is dependent on production of endogenous ethylene. The following evidence is consistent with the hypothesis that the activity of RNase is regulated at transcription. (a) Wound induction of RNase is inhibited by actinomycin D (ACTD), cordycepin, or α-amanitin. (b) Addition of ACTD at 9, 12, or 24 hours causes an immediate decline in RNase. (c) Six measurements of the natural decline in RNase between 24 and 36 hours show a t(0.5) of 14.1 ± 1 hour. (d) Use of proecdures for measurement of the t(0.5) for degradation of mRNA in bacteria and plants show a mean t(0.5) of 14 ± 1 hour for degradation of RNase mRNA in presence of ACTD. From the fact that both the degradation of RNase in presence of ACTD and the natural decline in RNase have a t(0.5) that is very similar to the t(0.5) for degradation of RNase mRNA, it is postulated that the natural decline in sweet potato RNase is due to repression of the RNase gene as a result of which the rate of degradation of RNase follows the t(0.5) for degradation of RNase messenger.